圆弧齿线圆柱齿轮传动副建模及接触强度分析 - 李波; 侯力; 姜平; 魏永峭; 贾凤兰; 牟如强 (Jixie Chuandong, 2014)
Based on analyzing processing principle of cylindrical gears with arcuate tooth trace and meshing theory of ideal gear,the cylindrical gears with arcuate tooth trace geometry parameters are got.Based on three-dimensional modeling software UG NX8.0,its virtual prototyping are completed.The impact mechanism of variable radius on tooth line,modulus and tooth width of cylindrical gears with arcuate tooth trace are researched via finite element analysis method.According to analysis,the cylindrical gears with arcuate tooth trace teeth wire radius,modulus and tooth width have a close relationship with their contact strength,and when the other relevant parameters are certain and 1.1b≤RT≤2b,the contact stress value is of the minimum.Therefore,the theoretical basis for design and industrial applications of cylindrical gears with arcuate tooth trace is provided.